Application of the health belief model in developing a community-based health literacy kit for diabetes prevention - Darmawan, Armaidi; Syauqy, Ahmad; Justisia, Budi; Gading, Patrick Wiliam; Aurora, Wahyu Indah Dewi; Kusdiyah, Erny; Witri, Repelita (Proceedings Academic Universitas Jambi, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) remains a major global and national health challenge, particularly in Indonesia where the prevalence has reached 10.6%. Low health literacy among high-risk populations limits preventive efforts and self-management. Objective: This study aimed to apply the Health Belief Model (HBM) in developing a culturally contextualized health literacy kit for diabetes prevention and to evaluate its theoretical relevance, content validity, and practical feasibility. Methods: A mixed-method design was employed involving 10 health educators and 60 high-risk community members recruited purposively. The development process consisted of five stages: needs assessment, prototype design, expert validation, limited trial, and revision. Data were collected through questionnaires, expert validation sheets, focus group discussions, and pre–post knowledge tests. The kit was assessed using the Content Validity Index (CVI), and quantitative data were analyzed using paired t-tests. Results: The health literacy kit achieved a CVI score of 0.87, indicating strong content validity. Participants’ knowledge increased by 17.4% (p < 0.001), diabetes risk awareness by 22%, and healthy behavior intention by 19% after the intervention. Qualitative feedback supported the clarity, cultural relevance, and usability of the materials. Conclusion: The integration of all six HBM constructs effectively enhanced cognitive and motivational engagement in diabetes prevention. The developed kit proved feasible for community-based health education and can serve as a model for culturally sensitive interventions in other chronic disease prevention programs.